2015
DOI: 10.1097/scs.0000000000001540
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Aspect and iNOS and Bax Expression Modification in Bone Tissue Around Dental Implants Positioned Using Piezoelectric Bone Surgery Versus Conventional Drill Technique

Abstract: Even if the insertion protocol does not seem to significantly interfere with the long-term healing process, implant site preparation through the piezoelectric bone surgery technique may allow a reduction of peri-implant bone tissue inflammation and support a more rapid bone tissue healing phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 33 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…The relationship between these two conditions is influenced by the absence of micromovements of the implant after its placement into the preparation site [3]. Implant stability is influenced by several factors: bone density [4], implant macro-and micro-geometry [5,6], and surgical technique [7][8][9]. In the case of poor bone quality, or immediate post-extraction implants, the primary stability could be improved by the selection of a specific implant geometry and thread design.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between these two conditions is influenced by the absence of micromovements of the implant after its placement into the preparation site [3]. Implant stability is influenced by several factors: bone density [4], implant macro-and micro-geometry [5,6], and surgical technique [7][8][9]. In the case of poor bone quality, or immediate post-extraction implants, the primary stability could be improved by the selection of a specific implant geometry and thread design.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Misch classification (1988), the decreased bone density and the lack of bone cortical, such as D4 bone type, could influence the obtaining of primary stability during the implant positioning [9]. Several techniques had been proposed to increase primary stability in vivo in maxillary posterior region such as: under-preparation drilling protocols, manual condensation osteotomy, piezoelectric devices [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…9 –11 In the same way, a poor bone density is associated to a more difficult primary stability achievement. 12 –15 Comuzzi et al reported that, in standardized condition on low-density polyurethane study, the macro-geometry induced the main effect on the primary stability, while the osseodensification drilling procedure produced the more visible effect on stability in presence of a residual cortical bone. 16 Moreover, Gehrke et al reported the key role of the implant macro-geometry on a sheep study, while the self-tapping and round apex macro-geometry is able to influence significantly the percentage of new bone formation and the deposition of highly vascularized osteogenic matrix within the marrow spaces, 17 where the number and thickness of bone trabeculae increase with the loading of the dental implants.…”
Section: Introductionmentioning
confidence: 99%